Health‐related quality of life in patients with Duchenne muscular dystrophy: a multinational, cross‐sectional study. (19th October 2015) - Landfeldt, Erik; Lindgren, Peter; Bell, Christopher F; Guglieri, Michela; Straub, Volker; Lochmüller, Hanns; Bushby, Katharine
Abstract : Aim: To estimate health‐related quality of life (HRQOL) in patients with Duchenne muscular dystrophy (DMD). Method: HRQOL was assessed using the Health Utilities Index Questionnaire (HUI) and the Pediatric Quality of Life Inventory (PedsQL) neuromuscular module version 3.0 online. Results were stratified by disease stage (early/late ambulatory/non‐ambulatory) and caregivers' perceptions of patients' health and mental status. Results: A total of 770 patient–caregiver pairs (173 German, 122 Italian, 191 UK, and 284 USA) participated. Most caregivers (>84%) perceived their patients as happy/somewhat happy and in excellent/very good/good health, irrespective of current ambulatory class. In contrast, mean patient utility (reflecting public preferences: 0, dead; 1, perfect health) deteriorated with disease course, from 0.75 in early ambulatory males to 0.15 in the most severely affected patients. Mean patient PedsQL scores (0–100, higher score indicating better HRQOL) decreased from 80 to 57 across ambulatory classes. Interpretation: HRQOL in DMD, measured through public preferences, is substantially impaired in relation to the general population and significantly associated with disease progression. Still, most patients are perceived as happy and in good health by their caregivers, indicating that influential domains of HRQOL remain intact through the disease progression. Our findings emphasize the challenges in measuring HRQOL in a rare, progressive childhood condition such as DMD. What this paper adds: Duchenne muscular dystrophy has a detrimental impact on health‐related quality of life (HRQOL) measured through public preferences. HRQOL measured through public preferences deteriorates with disease progression. Still, most caregivers perceive patients as happy and in good health. Our data suggest patients adapt to their changing health states. Measuring self‐perceived HRQOL in a rare, genetic disease is challenging. This article is commented on by Pangalila on pages435–436 of this issue.